Account of the Discovery of a Cinerary Urn with other Relics, near Marchhouse, Muirkirk, and the Excavation of an Earth-house at Yardhouses, Carnwath - Fairbairn, Archibald (Proceedings of the Society of Antiquaries of Scotland, 1924)
The urn, on discovery by workmen, was in an inverted position, covering a large deposit of burnt bones, and containing as well a small urn of the incense-cup type, an unburnt bone pin polished and pointed at one end, a bronze awl pointed at one end and flattened at the other, and an unworked flake of chert. Detailed investigation revealed a second urn with burnt bone. Both had been buried within a cairn, now almost totally denuded. The stone-built earth-house comprised a single chamber and a passageway. The roof of the chamber had not survived. Pottery, charcoal and animal bone were recovered.